Effect of Dietary Supplementation of Rumen Protected Calcium Salts of Rapeseed Oil and Encapsulated Rapeseed Oil to Lactating Dairy cows - Subrahmanyeswar, G; S, Senthil Murugan; Chacko, Biju; K, Shyama (Indian Journal of Animal Nutrition, 2019)
The present study examined the effects of rumen protected rapeseed oil supplementation on dry matter intake, milk yield and milk composition in dairy cows. Eighteen lactating crossbred Holstein Friesian cows were randomly divided into three experimental groups GI, GII and GIII. Control group (G I) was fed with basal diet without rumen protected fat. The encapsulated and calcium salts of rapeseed oil was prepared as rumen protected fat and hand mixed with concentrate mixture fed to experimental cows in GIII and GII groups respectively at 20 g/kg milk/day for a period of 90 days. The experimental animals in G III daily dry matter intake (DMI) (11.50 ± 0.060) (kg/cow/day) was significantly (P